Integrating African Pentecostalism into the theological education of South African Universities: An urgent task - Kgatle, Mookgo S. (HTS teologiese studies, 2018)
African Pentecostalism continues to be a growing part of Christianity both in Africa and the rest of the world. Pentecostal churches in Africa are on the rise at a very high rate. However, theological education in South African universities does not reflect this reality, but continues to be of a western orientation. Therefore, there is an urgent need and demand for a theological education that will be relevant to Africa. It is an urgent need for African Pentecostalism to be integrated into the theological education of South African universities. This can be achieved by integrating African Pentecostalism into the curriculum, by decolonising Pentecostal research and by the emergence of critical African scholars that can address cutting-edge issues in a South African context. Thus, theological education in South African universities shall be a contextual and relevant one.